Search for CP violation in t t ¯ $$ \overline{t} $$ H and tH production in multilepton channels in proton-proton collisions at s $$ \sqrt{s} $$ = 13 TeV - The CMS collaboration; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; A. Escalante Del Valle; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Journal of High Energy Physics, 2023)
Abstract The charge-parity (CP) structure of the Yukawa interaction between the Higgs (H) boson and the top quark is measured in a data sample enriched in the t t ¯ $$ \overline{t} $$ H and tH associated production, using 138 fb −1 of data collected in proton-proton collisions at s $$ \sqrt{s} $$ = 13 TeV by the CMS experiment at the CERN LHC. The study targets events where the H boson decays via H → WW or H → ττ and the top quarks decay via t → Wb: the W bosons decay either leptonically or hadronically, and final states characterized by the presence of at least two leptons are studied. Machine learning techniques are applied to these final states to enhance the separation of CP -even from CP -odd scenarios. Two-dimensional confidence regions are set on κ t and κ ~ $$ \overset{\sim }{κ } $$ t, which are respectively defined as the CP -even and CP -odd top-Higgs Yukawa coupling modifiers. No significant fractional CP -odd contributions, parameterized by the quantity | f CP Htt $$ {f}_{CP}^{Htt} $$ | are observed; the parameter is determined to be | f CP Htt $$ {f}_{CP}^{Htt} $$ | = 0.59 with an interval of (0.24, 0.81) at 68% confidence level. The results are combined with previous results covering the H → ZZ and H → γγ decay modes, yielding two- and one-dimensional confidence regions on κ t and κ ~ $$ \overset{\sim }{κ } $$ t, while | f CP Htt $$ {f}_{CP}^{Htt} $$ | is determined to be | f CP Htt $$ {f}_{CP}^{Htt} $$ | = 0.28 with an interval of | f CP Htt $$ {f}_{CP}^{Htt} $$ | < 0.55 at 68% confidence level, in agreement with the standard model CP -even prediction of | f CP Htt $$ {f}_{CP}^{Htt} $$ | = 0.